High throughput chirped pulse Fourier-transform microwave spectroscopy of ethanol and water clusters. Issue 22 (26th May 2022) - Dutton, S. E.; Blake, G. A.
Abstract : A rotational study of low energy conformers of (CH3 CH2 OH)3 and (CH3 CH2 OH)2 H2 O via the design and construction of a novel instrument for CPFTMW. Abstract : Here we discuss the design and performance of a novel high-throughput instrument for Chirped Pulse Fourier-transform Microwave (CP-FTMW) spectroscopy, and demonstrate its efficacy through the identification of the lowest energy conformers of the ethanol trimer and mixed water : ethanol trimers. Rotational constants for these trimers were calculated from observed lines in the spectra from 10 to 14 GHz, and compared to the results of anharmonic ab initio computations. As predicted, all trimers share a cyclic donor–acceptor hydrogen bonding structure, with the ethanol monomer favoring the gauche conformation in the lowest energy structures. The increased speed of data collection and resulting sensitivity opens a new avenue into rotational studies of higher order clusters.